Regenerating the Cardiovascular System Through Cell Reprogramming; Current Approaches and a Look Into the Future - Tsifaki, Marianna; Kelaini, Sophia; Caines, Rachel; Yang, Chunbo; Margariti, Andriana (Frontiers in Cardiovascular Medicine, 2018)
Cardiovascular disease (CVD), despite the advances of the medical field, remains one of the leading causes of mortality worldwide. Discovering novel treatments based on cell therapy or drugs is critical, and induced pluripotent stem cells (iPS Cells) technology has made it possible to design extensive disease-specific in vitro models. Elucidating the differentiation process challenged our previous knowledge of cell plasticity and capabilities and allows the concept of cell reprogramming technology to be established, which has inspired the creation of both in vitro and in vivo techniques. Patient-specific cell lines provide the opportunity of studying their pathophysiology in vitro, which can lead to novel drug development. At the same time, in vivo models have been designed where in situ transdifferentiation of cell populations into cardiomyocytes or endothelial cells (ECs) give hope towards effective cell therapies. Unfortunately, the efficiency as well as the concerns about the safety of all these methods make it exceedingly difficult to pass to the clinical trial phase. It is our opinion that creating an ex vivo model out of patient-specific cells will be one of the most important goals in the future to help surpass all these hindrances. Thus, in this review we aim to present the current state of research in reprogramming towards the cardiovascular system’s regeneration, and showcase how the development and study of a multicellular 3D ex vivo model will improve our fighting chances.